(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
Hospitalization plays an important role in the care for children’s health, especially children that require intensive medical care. In comparison to adults, as a result of the insufficient emotional and cognitive maturation on the one hand and the lack of sufficient and appropriate information on the other side, children are significantly more influenced by hospitalization and its associated factors. In addition to having to face the normal developmental lawfulness, hospitalized children also have to face the challenges of separation from their home and family, hospitalization, illnesses and clinical procedures that they will undertake. The intensity and the type of the psychosocial reaction of children to the hospitalization depends on significant variables such as the child’s age, gender, personality traits, type and severity of the illness, type of treatment, duration of the inpatient length of stay and the time organization in the hospital. The hospitalization usually has a negative impact on the motor, cognitive, emotional and social development of the child. Most negative experiences of hospitalization are due to poor attention to the developmental needs of children in health care planning in hospitals and bad organization of the leisure time.